1996
DOI: 10.1530/jrf.0.1060299
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake and carbohydrate metabolism by in vitro derived bovine embryos

Abstract: The consumption of oxygen, uptake of pyruvate and glucose and production of lactate were determined for groups of bovine embryos produced in vitro from the one-cell to the blastocyst stage (day 0\p=n-\6of culture). Measurements were made in Hepes-buffered synthetic oviduct fluid medium supplemented with 1.0 mmol pyruvate l \ m=-\ 1, 10 mmol d,l-lactate l \m=-\1 and 1.5 mmol glucose l \m=-\1and also 3 mg BSA ml \m=-\1and, from day 5 of development, 10% (v/v) fetal calf serum. The amount of ATP production was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
175
3
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(208 citation statements)
references
References 3 publications
16
175
3
6
Order By: Relevance
“…The rate of oxygen consumption in embryos at 38.5 8C was , 2.8 ÂŁ 10 213 moles/s. This value is closer to the value of 0.14 ÂŁ 10 213 moles/s for bovine morula reported by Shiku et al (2001) than for values reported by Thompson et al (1996) of , 9 ÂŁ 10 211 moles/s for bovine embryos from day 0 -4 of culture. Reported values for bovine blastocysts range from 0.4 -1.5 ÂŁ 10 29 moles/s , Kaidi et al 2001, Donnay et al 2002.…”
Section: Discussionsupporting
confidence: 63%
“…The rate of oxygen consumption in embryos at 38.5 8C was , 2.8 ÂŁ 10 213 moles/s. This value is closer to the value of 0.14 ÂŁ 10 213 moles/s for bovine morula reported by Shiku et al (2001) than for values reported by Thompson et al (1996) of , 9 ÂŁ 10 211 moles/s for bovine embryos from day 0 -4 of culture. Reported values for bovine blastocysts range from 0.4 -1.5 ÂŁ 10 29 moles/s , Kaidi et al 2001, Donnay et al 2002.…”
Section: Discussionsupporting
confidence: 63%
“…The increase in oxidative activity observed in sperm-activated oocytes corresponds to the initiation of pronuclear formation and first mitotic division in putative zygotes, suggesting increased demands for energy for these events. It has been observed that one-and two-cell bovine embryos are dependent on mitochondrial oxidative phosphorylation for energy supply, consuming oxidative substrates to produce ATP (Kim et al 1993, Thompson et al 1996. Coincidently, a higher oxygen consumption rate was detected before cleavage in bovine zygotes (Lopes et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen Consumption-Rates of oxygen consumption by embryos were assessed by an non-invasive pyrene method (10,11). Embryos were incubated in 2 l of media in a 5-l polymerase chain reaction micropipette loaded with 1 l of pyrene (Sigma) dissolved in paraffin oil (BDH) that had been pregassed overnight in a gas phase of 20% oxygen, and each end of the tube was then sealed (10).…”
Section: Media-mentioning
confidence: 99%
“…For each experiment a control of 1 mg/ml yeast that had been incubated overnight in 60 mM glucose for zero oxygen and a 20% oxygen control where the PCR tube was loaded with medium and no embryos were included. The levels of oxygen consumption were then calculated by using a program that relates the linear change in pyrene fluorescence to changes in oxygen levels and models the diffusion of oxygen along the length of medium and pyrene (10,11). Oxygen consumption was ex- Enzyme Extraction-For whole embryo extraction, individual embryos were washed in saline and placed in 500 nl of enzyme extraction buffer containing 100 mM K 2 HPO 4 , 30 mM KF, 1 mM EDTA, 5 mM mercaptoethanol, 2 g/liter bovine serum albumin, and 0.5 g/liter phenylmethylsulfonyl fluoride at pH 7.5 (12).…”
Section: Media-mentioning
confidence: 99%